O que textos fazem e como se fazem textos em uma sala de aula de ciências da natureza: um estudo de práticas sociais relacionadas à escrita - Bianca Alves Dell Aretti (2008)
The written language is an important instrument of communication at school. However, when learning science, activities involving the written language seem to be limited and restricted to an impersonal standard of writing. In this research, we intended to investigate how practices of production of written texts influence and determine aspects of a science classrooms culture in middle school. In particular we examined aspects such as the roles members assume as well as interaction patterns and practices. This is a study oriented by a socio-historical approach and an ethnographic perspective, having as its major reference the interactional ethnography. All concerns had been taken to assure the welfare of the participants. We used multiple instruments for data collection: participant observation, audio and video recording, field notes, written documents and semi-structured interviews. In the classroom we studied, writing had a central role, however, we identified limited diversity in the practices of production of texts. Thus, we conceive activities of intervention, in which the pupils would have greater opportunities for authorship. We contrasted one of these activities with practices that were more commonly addopted. We identified differences in relation to four aspects: the ways the teacher organized the physical space of the classroom during activities; the denominations attributed by the participants to the activities; the ways the teacher oriented pupils and the ways students participated. In relation to the physical space, the teacher maintained some patterns of organization, but in the intervention activity she tried to share with pupils her views about the relationships between the organization and their learning. Pupils and the teacher nominated the intervention activity in different ways, which reflected different conceptions of sciences. Our results indicate that the different texts created opportunities for the members of that community a new ways to engage in different ways in the science activities, extending the forms of participation of pupils in classroom.